PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN BARANG KONSUMSI YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2018-2020 - Mirza Abdi Khairusy; Nugraha Nugraha; Ahmad Johan; Mayasari Mayasari (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
In research on sales growth and company measurements on the capital structure of goods companies, the aim is to identify the effect of the growth variable of each sales and the size variable in each company on the capital structure variable. This research is included in the type of causal and population research in the study, namely companies for consumer goods (Customer Good Industry) listed on the Indonesia Stock Exchange for the period 2018 - 2020 as many as 23 companies. The data used are secondary data using multiple regression analysis, and partial test (t test) using the SPSS (Statistical Package for the Social Sciences) 26 for windows program. The results of the study partially that the Sales Growth Variable has a significant positive effect on the Capital Structure Variable, the Size Variable in the company which has a significant effect on the Capital Structure Variable so that simultaneously on the sales growth variable and the Company Size Variable which affects the Capital Structure Variable.